The All-American Muscle Car : The Rise, Fall and Resurrection of Detroit's Greatest Performance Cars - Revised & Updated /: The Rise, Fall and Resurrection of Detroit's Greatest Performance Cars - Revised & Updated. (2017) - Oldham, Joe; Wangers, Jim; Comer, Colin; Newhardt, David; Leffingwell, Randy
No abstract available